Evaluasi Pengalaman Belajar Mahasiswa Dalam Penggunaan Kamus Digital Jamak Taksir Pada Pembelajaran Kitabah - Joni Kawijaya; Lukman Habibul Umam; Mulyono (CV JK Riset Publishing Group, 2026)
The utilization of digital technology in Arabic language learning, particularly digital dictionaries for jamak taksir (broken plurals), significantly depends on user experience (UX). This study aims to evaluate students' learning experiences using a jamak taksir digital dictionary in kitabah (writing) instruction at IAI Darul A’mal Lampung. Employing a descriptive quantitative approach, data were collected from 10 students via Likert-scale questionnaires and observations, then analyzed using SPSS. The results indicate that the user experience falls into the